Development of E-Learning Technology in Designing and Making E-book-Based Learning Modules in Audio Video Engineering Subjects to Increase Student Learning Creativity - Adila, Diena Rahma; Basori, Basori; Liantoni, Febri Liantoni (Politeknik NEST, 2024)
E-book learning media is very necessary at this time because it has the advantage of being more interactive and efficient, it can also create teaching and learning activities that are more effective compared to printed books. With problems with the learning system implemented at SMK Negeri Kartoharjo, they still use package books , making students feel bored. The purpose of this study (1) to find out how to design e-book-based learning modules in TAV subjects to increase student creativity, (2) to find out how to make learning modules in the development of e-learning technology in the form of e-books on TAV subjects to enhance students' learning creativity. This research is research and development. The data collection techniques used are observation, questionnaire, literature, type of data. The subjects involved consisted of 1 media expert, 1 material expert, and 56 learners. The resulting data is in the form of quantitative data and qualitative data. The results of the due diligence by material experts obtained 90% in the category of very feasible, and by media experts obtained 89.75% in the category of very feasible, for the small group test gained 89% in the very decent category. It can be concluded that the media in the form of ZmarTAV digital books is included in the category of very worthy to be used as a learning medium for audio and video processing techniques in video editing materials using video processing software